STUDY OF ANTIOXIDANT, CYTOTOXIC AND ANTIMICROBIAL ACTIVITIES OF EXTRACTS OBTEINED FROM ACHILLEA MARITIMA (L.) EHREND. & Y.P.GUO (ASTERACEAE) - Bilgi, Selçuk; Beyatli, Ahmet (Химия растительного сырья, 2023)
Various extracts obtained from Achillea maritima analyzed with HPLC-DAD method to detect phenolic compounds. Total phenolic content (954.94±38.36 mg/g sample) and antioxidant activity results of A. maritima (604.15±11.57 mg trolox/g sample for DPPH method, 347.65±8.98 mg trolox/g sample for ABTS method, 486.31±9.99 mg trolox /g sample for FRAP method) were found in ethyl acetate extract the most. In addition, phenolic acid and ferulic acid was determined as the major phenolic substance (47.97±0.07 mg/g sample). The ethanol and chloroform phases showed MIC values of 2500 µg/mL against bacteria and fungus, and the hexane phase showed MIC values of 19, 39, 156 µg/mL against S. aureus, E. fecalis and P. aeruginosa, respectively. Ethyl acetate phase has a various activity against each bacteria. Butanol phase was found to be more effective against Gram-negative (MIC 625 µg/mL and 39 µg/mL) than Gram-positive ones (MIC 1250 µg/mL). The water phase had a stable MIC (625 µg/mL) against all strains. In MTT test, extracts showed different levels of cytotoxicity (240–820 µg/mL) against K562 and Saos cell lines, while extracts were non-toxic against NIH-3T3. In Brine shrimp assay ethanol, hexane and chloroform extracts had a moderate cytotoxic effect.